VISUALISASI DAMPAK NEGATIF BERMAIN JUDI ONLINE DALAM BIDANG SOSIAL DAN MATERI BERUPA FILM PENDEK - Adrian, Muhammad Yafi; Trihanondo, Donny; Zen, Adrian Permana (eProceedings of Art & Design, 2024)
Abstract: Online gambling involves wagering money or valuable items with the hope of winningsubstantial prizes, heavily reliant on luck. However, if luck is not on one's side, the risk of losing allbets becomes significantly high, even potentially leading to bankruptcy. The ease of accessingonline gambling through electronic devices like phones and computers connected to the internetfurther boosts its popularity. A short film titled "Hope and Reality" is part of a final project,narrating the story of an individual trapped in online gambling, resulting in addiction and theemergence of various problems in their life. This film provides insights into the risks faced by youngpeople involved in online gambling. In this film, emphasis is placed on the aspect ofcinematography to deliver a profound visual experience. The purpose of this work is to portray thefeelings and experiences of individuals before, during, and after engaging in online gamblingthrough the medium of a short film. Through elements of cinematography, the film conveys howchanges in emotions can be reflected in the surrounding environment.Keywords : Online Gambling, Short Film, Cinematography